abroad - Lidin, Konstantin (project baikal, 2019)
At first glance it would seem that small towns in Europe live in the reality that has nothing to do with the Russian reality. The Western Drift brings polarization along the east-west line and concentrates population in the central regions of the continent. The cities of Eastern and Southern Europe become deserted and desperately vie for outflowing inhabitants. Together with people, life flows out of the towns of the Baltic, Tanscaucasia and the Black Sea region, leaving behind nothing but sad nostalgia. On the contrary, Western Europe is overcrowded with newcomers. This wave of immigrants and tourists is going to “swallow” the traditional style of life. But if we look closer, the universal human nature of the situation concerning small towns will become obvious. To save diversity and identity, the whole range of individual features accumulated by small towns in all regions is our duty and a required element of today’s and tomorrow’s development.